Die casting alloy

By using a composition of iron, magnesium, silicon and other elements in the die-cast alloy, and the formation of the eutectic alloy Al14Fe3, the problem of difficult use of low-quality waste aluminum in the prior art is solved, and an efficient and environmentally friendly casting effect is achieved.

CN119824280APending Publication Date: 2025-04-15ALUMINUM RHEINFELDEN ALLOYS GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411429510.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-13
Filing Date
2024-10-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize low-quality scrap aluminum, especially scrap aluminum containing high-speed iron or other impurities, which makes it unavailable in casting and cannot meet the environmentally friendly and cost-effective casting alloy needs.

Method used

A die-cast alloy composition is proposed, which consists of elements such as iron, magnesium, silicon, calcium, zinc, copper, manganese, nickel, etc., and through the formation of the eutectic alloy Al14Fe3, the tendency of aluminum to shrink and adhere to the mold is reduced, and casting and corrosion resistance are improved.

Benefits of technology

It achieves the use rate and casting efficiency of recycled aluminum without damaging strength, ductility, corrosion resistance and processability, and reduces manufacturing costs and energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005083215990000061
    Figure BDA0005083215990000061
  • Figure BDA0005083215990000071
    Figure BDA0005083215990000071
  • Figure BDA0005083215990000072
    Figure BDA0005083215990000072
Patent Text Reader

Abstract

According to the invention, the following composition is proposed for the die casting alloy: iron (Fe) 0.8-2.0 wt% of magnesium (Mg) 0.3-6.0 wt% of silicon (Si) 0.3-1.2 wt% of calcium (Ca) 0.05-2.0 wt% of zinc (Zn) 0-4.0 wt% of copper (Cu) 0-2.5 wt% of manganese (Mn) 0-1.5 wt% of nickel (Ni) 0-0.6 wt% 0-0.8% of one element or group of elements selected from chromium (Cr), lead (Pb), lithium (Li), vanadium (V), titanium (Ti), phosphorus (P), molybdenum (Mo), zirconium (Zr), gallium (Ga), the remainder being aluminum and unavoidable impurities.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention relates to a die-casting alloy based on aluminium, iron, magnesium and silicon.

[0002] The aluminum foundry industry plays a vital role in various application fields, from the automotive industry to electronic devices. In recent years, the demand for environmentally friendly and cost-effective casting alloys, especially die casting alloys, has increased. One of the challenges lies in enabling the use of low-quality recycled aluminum, which is obtained from aluminum scrap from various sources, to reduce waste and use resources more efficiently.

[0003] According to the prior art, scrap wheels are used to produce AlSi9MnMg alloys with a high recycling content, in particular because this type of scrap has a low iron content. Other types of scrap with higher iron or other impurities are generally not available.

[0004] From EP 3235916 B1 a die-casting alloy based on aluminium, iron and magnesium is known which is used in particular in the field of vehicle structural components.

[0005] An object of the present invention is to provide an alloy composition having a high secondary aluminum content without undue compromise in properties such as strength, ductility, corrosion resistance and machinability.

[0006] The die casting alloy of the present invention is composed of the following elements:

[0007] Iron (Fe) 0.8-2.0 wt%

[0008] Magnesium (Mg) 0.3-6.0 wt%

[0009] Silicon (Si) 0.3-1.2 wt%

[0010] Calcium (Ca) 0.05-2.0 wt%

[0011] Zinc (Zn) 0-4.0 wt%

[0012] Copper (Cu) 0-2.5 wt%

[0013] Manganese (Mn) 0-1.5 wt%

[0014] Nickel (Ni) 0-0.6 wt%

[0015] 0-0.8% is one element or element group selected from the following: chromium (Cr), lead (Pb), lithium (Li), vanadium (V), titanium (Ti), phosphorus (P), molybdenum (Mo), zirconium (Zr), gallium (Ga), and the balance is aluminum and inevitable impurities.

[0016] One embodiment of the die casting alloy of the invention has a silicon content of 0.4-0.9 wt. % silicon.

[0017] Another embodiment of the die casting alloy according to the invention has a silicon content of 0.5-0.8% by weight of silicon.

[0018] Another embodiment of the die casting alloy according to the invention has an iron content of 1.0-1.7 wt. % iron.

[0019] Another embodiment of the die casting alloy according to the invention has an iron content of 1.1 to 1.5 wt. % iron.

[0020] Another embodiment of the die casting alloy according to the invention has a magnesium content of 2.5-6.0 wt. % magnesium.

[0021] Another embodiment of the die casting alloy according to the invention has a magnesium content of 3.5-5.0 wt. % magnesium.

[0022] A further embodiment of the die-casting alloy according to the invention has a calcium content of 0.08-1.5% by weight calcium, preferably 0.1-1.0% by weight calcium, particularly preferably 0.1-0.5% by weight calcium.

[0023] Another embodiment of the die casting alloy according to the invention has a vanadium content of 0.01-0.05 wt. % vanadium.

[0024] Another embodiment of the die casting alloy according to the invention has a zinc content of 0-1.0 wt. % zinc.

[0025] Another embodiment of the die casting alloy according to the invention has a zinc content of 0.1-0.5% by weight zinc.

[0026] Another embodiment of the die casting alloy according to the invention has a manganese content of 0.1-1% by weight manganese.

[0027] A further embodiment of the die-casting alloy according to the invention has a copper content of at most 2.0% by weight, preferably at most 0.1% by weight, copper.

[0028] A further embodiment of the die casting alloy according to the invention has a nickel content of up to 0.1% by weight nickel.

[0029] The alloy of the invention is a die casting alloy, or in other words, the alloy composition proposed by the invention is used for die casting, preferably for die casting of structural parts for automobile manufacturing. The term die casting alloy covers alloy compositions that are processed by the die casting process to form die casting parts. Die casting alloys must be clearly distinguished from wrought alloys. Die casting alloys are alloy compositions that are further processed by means of the die casting process in a one-step process to give the direct end product - the die casting part. The alloy composition can be introduced into the casting mold as a liquid melt or as a partially solidified melt.

[0030] If necessary, the product can be subjected to a subsequent heat treatment, or such a heat treatment can be deliberately avoided according to the invention. Moreover, the die-cast product in the as-cast "F state" already exhibits the desired material properties. An example of such a product is a die-cast structural component for an automobile.

[0031] The following die casting methods are examples of die casting processes: HPDC (High Pressure Die Casting), Vacuum Die Casting and Rheo Die Casting (also known as Reocasting), High Vacuum Die Casting.

[0032] In the die casting process, the molten alloy is usually injected into the mold at a high speed (called gate speed) of 20-100 m / s and solidified therein at a holding pressure of about 500-1000 bar. There are also process variants with a gate speed of only 1-10 m / s. In the case of aluminum, only cold chamber systems have been used so far. For larger casting weights, it is usually arranged horizontally, in some cases vertically or at an inclined angle.

[0033] The alloy of the invention is an alloy in which the aluminum comes from a secondary source. Secondary sources include scrap aluminum such as AlMg profiles, photolithographic material or scrap cans. According to DIN EN 13920-10, scrap cans include so-called UBC material (used beverage cans).

[0034] Die-cast structural parts for automobiles are components such as suspension strut domes, longitudinal beams or even larger components such as integral supports at the front or rear of the automobile.

[0035] Aluminum alloys used for automotive structural components typically have the following material properties:

[0036] Good castability, material properties Rm = 200-270MPa, Rp0.2 = 100-180MPa, A = 7-15%, good connection applicability (riveting, welding, gluing, etc.) and corresponding corrosion resistance.

[0037] Due to the composition of the invention, the final product exhibits a slightly increased strength compared to conventional casting alloys (e.g. AlSi alloys, which are also used for structural parts in automobile manufacturing). In addition, the alloy in the as-cast (F state) already has mechanical properties and no heat treatment is required, which reduces manufacturing costs and energy consumption.

[0038] Foundries require alloys with good castability. Usually, this is understood to mean that the alloy has good flowability when cast in die casting, good mold filling ability, good solidification characteristics (i.e., for example, low shrinkage and no tendency to cracking) and favorable properties when ejected from the mold (i.e., for example, low tendency to sticking). In actual casting trials, the alloy composition according to the invention can also show this.

[0039] The basis of the alloy composition of the present invention is an AlFe eutectic alloy, which exists mainly in the form of Al14Fe3, which ensures the castability of the alloy. It reduces the shrinkage of aluminum in the die casting mold and greatly reduces the tendency to stick in the mold (usually a steel mold). In addition to forming an Al14Fe3 eutectic alloy, the high iron content of the alloy of the present invention also results in low chemical attack on the mold steel. The consequence is a low necessary amount of release agent, low adhesion of the parts to the mold during ejection, and low mold wear. The formation of the eutectic alloy allows solidification to take place at a constant temperature. These properties of the alloy are described by experts as good castability. In addition, the alloy has no tendency to hot cracking in the temperature range of 250-500°C and has high formability. Both of these reduce the tendency to cold cracking during solidification, which also has a positive effect on castability.

[0040] Magnesium (Mg) acts as a solid solution strengthener to increase strength. Silicon (Si) also increases strength by forming Mg2Si together with magnesium (Mg). It has been found that despite the presence of silicon (Si), no embrittlement occurs, in particular no brittle AlFeSi phase is formed.

[0041] Calcium (Ca) reduces the oxidation tendency of the melt. In addition to calcium, the oxidation tendency of the melt can be further reduced by adding vanadium (V). Reducing the oxidation tendency of the melt also reduces magnesium smelting losses, thereby reducing magnesium losses during the production of the alloy composition of the present invention.

[0042] Other elements, while not absolutely necessary, may be tolerated to a greater extent than in other toughened die casting alloys, such as conventional AlSi alloys, which are often used as a standard for structural components in automotive manufacturing. These elements include, for example, the elements Mn, Cr, Cu and Zn.

[0043] Zinc provides a slight improvement in castability in terms of mold filling capability if Zn is present at 0.2-0.5%. Higher contents (3-4%) significantly increase the strength of the alloy, but also increase the susceptibility to corrosion.

[0044] It has been demonstrated that the influence of impurities on the corrosion tendency of the alloy of the present invention is less than that on the corrosion tendency of conventional AlSi alloys. The compositions are listed in Table 4. The alloy designated as M1 is an example of a conventional AlSi alloy compared with the compositions A1 and J2 of the present invention. Under normal conditions, a pH neutral salt spray test was performed for 720h on a die-cast plate of 3x 60x 60mm without surface treatment. Table 1 shows the weight loss before and after the test.

[0045] Table 1: Corrosion test results

[0046] Sample / Alloy <![CDATA[Weight loss [g / (m 2 day)]]]> A1 0.14 J2 0.32 M1 1.0

[0047] As expected, the corrosion resistance of alloy A1 is higher than that of alloy J2. J2 contains relatively high contents of Mn, Cu and Zn compared to alloy A1.

[0048] Surprisingly, the results show that the corrosion resistance of the alloy of the present invention is superior to that of the conventional AlSi alloy (see alloy composition M1), despite similar contents of Mn, Cu and Zn (see Table 4, M1, J2). In the alloy of the present invention, there is an insular structure of brittle, easily corroded intermetallic phases caused by impurities (e.g., the elements Fe, Mn, Cr and Cu form such phases). The aluminum phases between these phases prevent excessive reduction in ductility and excessive development of corrosive attack.

[0049] In alloy M1 (F state), intermetallic phases contaminated by impurities are often found in the AlSi eutectic alloy that is connected in a network-like manner throughout the material. This structure is more brittle and obviously more susceptible to corrosion.

[0050] Example of Embodiment The following table shows the composition of the waste cans (so-called UBC material, see the "Recycled Material" column) used for the alloy of the present invention. Examples of compositions of the present invention are listed in the "Alloy Composition J1" column. Depending on the composition of the recycled material, it is necessary to adjust the addition of the required alloying elements according to the known impurities (see the "Element Additions" column). In this example, the addition of just under 3.2% Mg has resulted in a yield tensile strength of more than 160 MPa. This strength cannot be achieved without the content of elements such as 0.23% Cu and 0.80% Mn in the starting alloy; a larger amount of Mg would have to be added.

[0051] Table 2 - Implementation 1

[0052] element Si Fe Cu Mn Mg Zn Recycled materials (UBC) 0.26 0.50 0.23 0.80 1.03 0.04 Alloy composition J1 0.53 1.21 0.23 0.79 4.20 0.04 Adding Elements have have none none have none element Cr Ni Ti Ca V Al Recycled Materials 0.02 0.01 0.02 0.00 0.00 margin Alloy composition J1 0.02 0.01 0.02 0.08 0.02 margin Adding Elements none none none have have none

[0053] Note: Other alloying elements are present in small amounts due to impurities.

[0054] For the compositions according to the invention listed in Table 2, the melting range (solidus-liquidus) was calculated by means of phase simulation to be 571-660° C. and the calculated heat of fusion was 485 kJ / kg. Despite the high impurity content, these values ​​indicate good castability during die casting. The heat of fusion is comparable to conventional AlSi alloys, which are rated by experts as having good castability. As an example, the heat of fusion of a rotor alloy rated as having poor castability is about 80 kJ / kg lower.

[0055] Table 3 discloses another example of the alloy composition of the present invention. As an example, the effect of adding Ca and V and the burning loss of magnesium will be explained here. Table 3A shows the composition of the alloy at the beginning of the test, and Table 3B shows the composition after 7 days.

[0056] Table 3-Implementation Plan 2 (Ca, V influence)

[0057] Table 3A At the start of the test

[0058] serial number. Si Fe Cu Mn Mg Ca V V1 0.036 1.54 0.001 0.005 4.26 0.000 0.023 V2 0.038 1.58 0.002 0.005 4.26 0.082 0.023

[0059] Table 3B 7 days after the end of the test

[0060] serial number. Si Fe Cu Mn Mg Ca V V1 0.04 1.64 0.001 0.005 3.18 0.000 0.022 V2 0.04 1.59 0.002 0.005 4.28 0.076 0.022

[0061] Tables 3A, 3B show the effect on magnesium burn-off. The addition of 0.082Ca and 0.023V already leads to a no longer significant loss of magnesium. In addition, it can be visually determined that the oxide layer on the melt is significantly reduced.

[0062] The results show that the combination of Ca and V (see V2) reduces the loss of Mg.

[0063] Adding V without adding Ca did not improve the oxidation tendency, i.e. the thickness of the oxide layer did not decrease. At the end of the test, the result was a significant loss of Mg (see V1).

[0064] Comparative Implementation

[0065] Table 4 compares the compositions of examples of alloys according to the invention. The values ​​are in weight %.

[0066] Table 4

[0067]

[0068]

[0069] Table 4 (continued)

[0070]

[0071]

[0072] Results

[0073] Mechanical properties (Rm, Rp0.2, A5) were measured on 3 mm die-cast plates for the cast samples in Table 4. Each cast sample shows an average value obtained from at least 6 tensile tests.

[0074] Despite the high recycling percentage and high contamination with different elements, the experimental results of the as-cast (F state) have yielded extraordinary mechanical properties (see Table 5).

[0075] Table 5 (Material properties, die casting, F state)

[0076]

[0077]

[0078] The castings from tests B1 and B3 were subjected to T5 heat treatment (1 h, 200° C.). The results are shown in Table 6 below:

[0079] Table 6

[0080]

[0081] The test results of heat treatment T5 (1h 200°C) show that compared with the F state, the tensile strength is almost unchanged, the yield tensile strength is slightly increased by 10-13MPa, and the elongation at break is reduced by 0.5-1.5%. Therefore, the alloy of the present invention can be used for structural parts in automobile manufacturing without heat treatment.

[0082] Recycled content indicates the approximate secondary aluminium content obtained from scrapped consumer products, so-called post-consumer recycling (PCR), without the use of industrial waste (pre-consumer recycling).

Claims

1. A die casting alloy consisting of the following components: Iron (Fe) 0.8-2.0 wt% Magnesium (Mg) 0.3-6.0 wt% Silicon (Si) 0.3-1.2 wt% Calcium (Ca) 0.05-2.0 wt% Zinc (Zn) 0-4.0 wt% Copper (Cu) 0-2.5 wt% Manganese (Mn) 0-1.5 wt% Nickel (Ni) 0-0.6 wt% 0-0.8% is one element or element group selected from the following: chromium (Cr), lead (Pb), lithium (Li), vanadium (V), titanium (Ti), phosphorus (P), molybdenum (Mo), zirconium (Zr), gallium (Ga), and the balance is aluminum and inevitable impurities.

2. The die casting alloy according to claim 1, characterized in that Silicon is 0.4-0.9% by weight.

3. The die casting alloy according to any one of the preceding claims, characterized in that Silicon is 0.5-0.8% by weight.

4. The die casting alloy according to any one of the preceding claims, characterized in that Iron is 1.0-1.7% by weight.

5. The die casting alloy according to any one of the preceding claims, characterized in that Iron is 1.1-1.5% by weight.

6. The die casting alloy according to any one of the preceding claims, characterized in that Magnesium is 2.5-6.0% by weight.

7. Casting alloy according to any one of the preceding claims, characterized in that Magnesium is 3.5-5.0% by weight.

8. Casting alloy according to any one of the preceding claims, characterized in that The amount of calcium is 0.08-1.5% by weight, preferably the amount of calcium is 0.1-1.0% by weight, and particularly preferably the amount of calcium is 0.1-0.5% by weight.

9. Casting alloy according to any one of the preceding claims, characterized in that Vanadium is 0.01-0.05% by weight.

10. Casting alloy according to any one of the preceding claims, characterised in that Zinc is 0-1.0% by weight.

11. Casting alloy according to any one of the preceding claims, characterised in that Zinc is 0.1-0.5% by weight.

12. Casting alloy according to any one of the preceding claims, characterised in that Manganese is 0.1-1% by weight.

13. Casting alloy according to any one of the preceding claims, characterised in that Copper is at most 2.0 wt %, preferably copper is at most 0.1 wt %.

14. Casting alloy according to any one of the preceding claims, characterised in that Nickel is at most 0.1 wt%.

15. Use of a casting alloy according to any of the preceding claims for die-casting structural parts for automobile production.

Citation Information

Patent Citations

  • Cast alloy

    EP3235916B1